Grace - Casanova, Mary. (Middleton, WI : American Girl Publishing, 2015)
Nine-year-old Grace likes having a plan but she must find a way to be flexible and open to new ideas when she goes to Paris with her mother and has trouble getting along with her cousin, while at home her friends start the business she proposed without her.
Keywords: Cousins -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Bakeries -- Juvenile fiction; Friendship -- Juvenile fiction; Paris (France) -- Juvenile fiction; France -- Juvenile fiction